Magyarországi települések vizsgálata közlekedési és távközlési ellátottság alapján - Miletics, Péter (Tér és Társadalom, 1996)
Transportation and telecommunication systems, as part of the infrastructure, play a considerable role in how individual settlements are judged. They increase the speed of the flows of information that gain greater and greater importance, in general, they improve the possibilities of information exchange. Furthermore they are dominant for the population, enabling them to expand their spatial moves and thus the increase in the mobility index of the population. The mere existence of these infrastructural elements does not enable a certain settlement to provide for independent space organising functions, but their possible lack has a much more negative impact on how the settlements are perceived than the really existing problems deriving from their maintenance or establishment. The selection of the 177 villages involved in the survey took place by preliminary agreements. Our purpose was to put the large villages by some arbitrarily chosen indices into a hierarchical order.